The Role of Accreditation in Transforming IAIN Lhokseumawe's PAI Quality - Wardhani, Nia; Safitri, Maya; Iqbal, Muhammad (ALACRITY : Journal of Education, 2025)
This study aims to analyze the implementation of accreditation in improving the quality of education in the Postgraduate Islamic Religious Education (PAI) Study Program at IAIN Lhokseumawe. Higher education accreditation is an important instrument to ensure the quality of education that is relevant to the needs of society and the development of the times. However, the implementation of accreditation often faces various challenges, such as the fulfillment of diverse quality standards and limitations in the management of accreditation data. The research method used is a qualitative approach with data collection techniques through interviews, observations, and document analysis. This study found that the Postgraduate PAI Study Program has tried to meet accreditation standards by improving the quality of the curriculum, management, and human resources. However, there are obstacles in the integration of internal and external quality evaluations and data management that still lack innovation. These findings suggest that accreditation should be seen as a strategic tool for a more holistic transformation of education, not just an administrative formality. This research is expected to contribute to improving the implementation of accreditation in higher education institutions, especially in Islamic-based study programs.